Circular RNA circSVIL Promotes Myoblast Proliferation and Differentiation by Sponging miR-203 in Chicken - Ouyang, Hongjia; Chen, Xiaolan; Li, Weimin; Li, Zhenhui; Nie, Qinghua; Zhang, Xiquan (Frontiers in Genetics, 2018)
Circular RNAs (circRNAs), expressed abundantly and universally in various eukaryotes, are involved in growth and development of animals. Our previous study on circRNA sequencing revealed that circSVIL, an exonic circular, expressed differentially among skeletal muscle at 11 embryo age (E11), 16 embryo age (E16) and 1 day post hatch (P1). In this study, we aim to investigate the effect of circSVIL on the development of skeletal muscle. We detected the expression level of circSVIL in embryonic leg muscle during E10 to P1. As a result, we found that circSVIL had a high expression level during late embryonic development of skeletal muscle. Through dual-luciferase assay, RNA immunoprecipitation and biotin-coupled miRNA pull down, we found chicken circSVIL could functions as miR-203 sponges and upregulated the mRNA level of c-JUN and MEF2C. In chicken, circSVIL could promote the proliferation and differentiation of myoblast, and antagonize the functions of miR-203. Altogether our data suggest that circSVIL promotes the embryonic skeletal muscle development by sequestering miR-203 in chicken.